Studies in Mathematics Education: Curriculum Analysis from Indigenous Knowledge and Gender Perspective - Abatar Subedi (Interdisciplinary Research in Education, 2021)
This paper aims to analyze the curriculum of the course ‘Studies in Mathematics Education (Math Ed. 539)’ from indigenous and gender perspectives. For, the curriculum of that course, particularly objectives, contents, textbooks, teaching/learning methods and evaluation are visualized and analyzed. The experiences and insights of two teachers of that course were included and analyzed concerning to IK and gender perspectives, by taking in-depth interviews with the help of semi-structured interview guidelines. The result shows that there are sufficient space and provision of incorporate IK in the curriculum and teachers are trying to implement this course as much as possible from the cultural perspective of mathematics education. The curriculum displays gender friendly and neutral aspects in terms of gender and teachers are using gender friendly methodology while implementing the course. However, the evaluation system is not more flexible as expected by female teacher. Thus, the inclusion of IK with particular local knowledge and making gender friendly curriculum is necessary for the courses of teacher preparation in mathematics education.